Electrical noise spectroscopy of magnons in a quantum Hall ferromagnet - Ravi Kumar; Saurabh Kumar Srivastav; Ujjal Roy; Jinhong Park; Christian Spånslätt; K. Watanabe; T. Taniguchi; Yuval Gefen; Alexander D. Mirlin; Anindya Das (Nature Communications, 2024)
Abstract Collective spin-wave excitations, magnons, are promising quasi-particles for next-generation spintronics devices, including platforms for information transfer. In a quantum Hall ferromagnets, detection of these charge-neutral excitations relies on the conversion of magnons into electrical signals in the form of excess electrons and holes, but if the excess electron and holes are equal, detecting an electrical signal is challenging. In this work, we overcome this shortcoming by measuring the electrical noise generated by magnons. We use the symmetry-broken quantum Hall ferromagnet of the zeroth Landau level in graphene to launch magnons. Absorption of these magnons creates excess noise above the Zeeman energy and remains finite even when the average electrical signal is zero. Moreover, we formulate a theoretical model in which the noise is produced by equilibration between edge channels and propagating magnons. Our model also allows us to pinpoint the regime of ballistic magnon transport in our device.